Public expenditure analysis - Shah, Anwar; World Bank. (Washington, D.C. : World Bank, 2005)
Explores two themes: the orientation of government towards its more vulnerable groups and the extent to which government is responsive to its citizens.
Includes bibliographical references and index.
oif 04/05/15
Loans
Keywords: Local government; Municipal services; Local budgets; Expenditures, Public